2019
DOI: 10.1136/oemed-2018-105405
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Saharan dust episodes on preterm births in Guadeloupe (French West Indies)

Abstract: ObjectivesLarge amounts of mineral dust are transported from their African sources in the Saharan-Sahel region to the Caribbean Sea, generating peak exposures to particulate matter ≤10 µm (PM10). This study aimed to investigate the impact of Saharan dust episodes on preterm births in the Guadeloupe archipelago.MethodsThe study population consisted of 909 pregnant women who were enrolled in the TIMOUN mother-child cohort between 2004 and 2007. Desert dust episodes were assessed from PM10 concentrations recorded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 19 publications
2
28
0
Order By: Relevance
“…The study population and exposure assessment have been fully described elsewhere. 8 In brief, 1,068 women were enrolled successively in the Timoun cohort during their third trimester prenatal visit, between 2004 and 2007. The participants were representative of pregnant women giving birth in the local public hospitals, which accounts for 70% of all deliveries in Guadeloupe.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study population and exposure assessment have been fully described elsewhere. 8 In brief, 1,068 women were enrolled successively in the Timoun cohort during their third trimester prenatal visit, between 2004 and 2007. The participants were representative of pregnant women giving birth in the local public hospitals, which accounts for 70% of all deliveries in Guadeloupe.…”
Section: Methodsmentioning
confidence: 99%
“…[2][3][4][5] Although an increasing number of studies have shown that maternal exposure to air PM can affect the developing fetus (resulting in, among other outcomes, small for gestational-age [SGA] births), 6 available evidence on the effects of dust outbreaks on pregnancy is very scarce. 7,8 We aimed to investigate the impact of Saharan dust episodes on severe SGA births among a population of pregnant women in the French Guadeloupe archipelago (an outermost region of the European Union situated in the Caribbean basin) using prospectively collected individual data.…”
Section: Introductionmentioning
confidence: 99%
“…Six articles discussed the long-term adverse health effects caused by dust storms by means of different outcomes, like reduced birth weight, baby’s birth weight <2.5 Kg, gestation/gestational age >37 weeks and premature birth, 32 and decreased cognitive function in children. 33 Preterm births 34 were correlated with Valley fever incidences 36 and increased spring measles incidence. 44 Only one article was observed to indicate no significant effect of desert dust storms on pregnancy consequences.…”
Section: Long-term Health Effectsmentioning
confidence: 99%
“… 24 , 26 , 30 In rare cases, it can even lead to death. 26 , 31 Evidence further suggests that frequent exposure to dust storms can lead to increased adverse health effects 24 , 32 - 37 in people of almost all age groups and genders. 3 , 38 , 39 People with a history of diabetes, hypertension, cerebrovascular, or pulmonary disease are also at higher risk.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to their global climate and ecosystem impact [95], they have been associated with adverse health effects, including cardiorespiratory mortality and morbidity [96]. Recently, Viel et al [97] also evidenced an increasing risk of preterm births with the levels of PM10 and the frequency of intense Saharan dust events over Guadeloupe Island.…”
Section: Saharan Dustmentioning
confidence: 99%